Color Association to Emotions of Chinese and Thai University Students - Choosri, Noppon; Laolee, Nilawan; Wannayot, Nitchanun; Supamanee, Pathomsakul (Asia Social Issues, 2023)
Color association with emotions is culturally universal. The primary objective of this study is to identify cultural differences in color-emotion associations in two study groups that have received limited research attention: Thai and Chinese university students. The study used a questionnaire to collect data, then applied quantitative data analysis to address how colors are used to represent specific emotions in each respondent group. The study also investigated whether color association with emotions in those two study groups is significantly different. The findings suggest that some colors have a very strong association to one culture such as 100% of Thai respondents used red to represent anger. The chi square test revealed a cross-cultural effect in color association. The color association in emotions that the two cultures studied differ significantly is red for anger. Purple for fear, green and white for happiness and black for sadness.